ICU SERVICE FINANCING: WEIGHING REGULATIONS AGAINST PROFESSIONAL JUDGMENT - Santoso, Widodo Mardi; Manzilati, Asfi; Ratri, Devita Rahmani; Hariyanti, Tita (Journal of Community Health and Preventive Medicine, 2025)
The Intensive Care Unit (ICU) is one of the most resource-intensive departments in a hospital. Patients admitted to the ICU incur, on average, three times higher costs than those in general wards. However, healthcare professionals, particularly doctors and nurses, often remain unaware of these high costs.   This study employs a qualitative research design using a case study approach. A total of seven participants were selected through purposive sampling. Data were collected through unstructured observations of the ICU environment and unstructured interviews with participants. Thematic analysis was then used to interpret the findings. Four key themes emerged: (1) The ICU as the last hope for survival, (2) Doctors and nurses feeling powerless over treatment costs, (3) The predominant focus of doctors and nurses on medical aspects, and (4) Sentosa Hospital: Between Regulation and Professionalism. The study was conducted at a provincial referral hospital, classified as a type A hospital and a teaching center, where patients present with complex medical conditions. This complexity often leads doctors and nurses to prioritize medical care over financial considerations. In conclusion, ICU doctors and nurses demonstrate limited awareness of the financial burden of patient care. To enhance this awareness, targeted interventions are needed to sensitize all healthcare professionals, particularly doctors and nurses, to the economic aspects of critical care.